Research Trends based on Technological Pedagogical Content Knowledge (TPACK) in Indonesia: A Systematic Review - Teguh Arie Sandy; Christina Ismaniati; Sukardi Abbas; Zaudah Cyly Arrum Dalu (Universitas Negeri Yogyakarta, 2023)
The integration of technology in education for a decade is increasingly needed, along with advances in the development of technology and information in the industrial era 4.0. One of the models used is the use of technological pedagogical content knowledge (TPACK) which has a very important role for learning in Indonesia. This study aims to provide a comprehensive view of research using TPACK in Indonesia and provide several possible directions for further TPACK research. A total of 745 documents were taken from the Google Scholar and Crossref databases related to research related to TPACK conducted in the period 2011 to 2022. This study used the PRISMA method in screening and obtained 90 articles that met the qualifications. The analysis related to TPACK is the number of years of research, distribution based on the journal category sinta, type of research, research targets, distribution of provinces, the most cited articles and journal that frequently publishes articles related to TPACK during 2011-2021 in Indonesia.